Teachers’ Challenges in ICT Integration for Early Childhood Education: A Systematic Literature Review - Hawa Nurul Jannah; Rita Mariyana; Moh Syaikhol Hadi (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Teachers still encounter obstacles when trying to include ICT into early childhood education, despite the growing importance of this practice in promoting digital literacy and age-appropriate learning. Researchers in this study want to learn more about current trends in the field and the obstacles that educators have when trying to include technology into their work with young children. Using the criteria outlined in PRISMA 2020, a systematic literature review was performed using 23 journal articles indexed by Scopus and published between 2016 and 2025. Studies that focused on teachers' experiences, both empirically and conceptually, made up the unit of analysis. Data were analyzed using thematic synthesis and bibliometric mapping to identify patterns and trends. The findings reveal growing research interest in ICT-ECE, alongside persistent barriers related to infrastructure, limited professional development, low TPACK levels, and difficulties aligning ICT with play-based pedagogy. These results imply the need for context-sensitive ICT integration models and sustained teacher capacity building to inform policy and practice.